The development of integrated Science Process Skills among primary pupils based on classroom assessment - Abu Bakar, Nuraini; Mustakim, Siti Salina; Hassan, Aminuddin; Razali, Fazilah (Turkish Online Jounal of Qualitative Inquiry, 2021)
The focus in science education for primary schools are scientific skills and thinking skills as the primary source of knowledge acquisition of science through inquiry approach. The Science Process Skills (SPS) are part of scientific skills that are needed to find answers to problems or making decisions systematically. Nevertheless, it has been found that the SPS achievement of primary school pupils remains unsatisfactory. Thus, this study focuses on the development of pupils’ integrated SPS via the implementation of a science curriculum in elementary school based on classroom assessment. Data were gathered from six teachers and twelve fifth-grade pupils selected purposively. The findings show four themes related to the development of pupils for integrated SPS; (1) pupils understanding towards six integrated Skills, (2) problems in mastering integrated SPS, (3) pupil’s effort to understand SPS and, (4) pupils ask friends to explain the SPS. As a conclusion, most of the pupils are not able to master the integrated SPS based on their responds and sharing session during the interview.